Productivity improvement in manufacturing SMEs : application of work study - Munyai, Thomas Thinandavha; Mbohwa, Charles; Mbonyane, Boysana Lephoi (Boca Raton, Fla. : CRC Press, 2018)
"This book focuses on the application of workstudy in productivity of manufacturing SMEs locally and abroad and also explores various industrial problems which face manufacturing SMEs in developing and underdeveloped countries in the rest of the world. Low productivity is currently a serious challenge facing manufacturing SMEs, where these SMEs are operating below expected production output levels which makes it difficult for them to compete in the global market. SMEs are the engine drivers of economic growth, one of which is manufacturing.The challenge is that government from various countries in developing and underdeveloped countries, mandated agencies in their respective areas, to ensure that there is economic progress for these SMEs, but productivity remains low in the manufacturing SMEs. When SMEs do not perform well, productivity of manufacturing SMEs declines and unemployment increases. Thus, an increase in unemployment results in a drop of GDP in the country and can become a global and economic crisis. This book describes a process which enables the reader to use effective knowledge that addresses problems facing the productivity of manufacturing SMEs such as work study tools and case studies and provides solutions and applications to improve the running of the manufacturing SMEs in growing their productivity. "--Provided by publisher.
chapter 1 Research Approaches and Main Results on Manufacturing SMEs in South Africa -- chapter 2 Productivity Theory and Work Study: Groundwork Theories -- chapter 3 Effectiveness versus Efficiency in Manufacturing SMEs: A Productivity Perspective -- chapter 4 Factors Influencing Productivity in Manufacturing SMEs -- chapter 5 Identifying the Environment for Manufacturing SMEs -- chapter 6 Work Study Techniques: Method Study -- chapter 7 Work Measurement (WM) Techniques -- chapter 8 Impact of Work Study on Physical Capital for Productivity in Manufacturing SMEs -- chapter 9 Impact of Work Study on Technological Capital for Productivity in Manufacturing SMEs -- chapter 10 The Impact of Work Study on Management in Relation to Productivity of Manufacturing SMEs -- chapter 11 Presentation and Report Writing in Manufacturing SMEs -- chapter 12 Conclusion and Further Research Studies.
Keywords: Industrial productivity; Performance -- Measurement; Small business; Manufacturing industries